(untitled) (Linguostylistic Studies, 2017)
The article reveals the features of the regulative money functioning in Lesia Ukrainka’s letters. The author defines the role of this regulative in the semantic system of the poetess’ epistolary text and determines the most expressive contexts of its explication. The emphasis is laid on the frequency of this lexeme nominative field components and their semantic and stylistic potential as well as individual author’s actualization of them. The productive attributive models that most fully reflect the personal orientations and convictions of the addressee were revealed with an emphasis on the addressee’s convictions concerning the recognition of the constant mutual conditionality of the opposites material / spiritual in private life of every person. According to Lesia Ukrainka, the status of “besserebrennik” (penniless person) has become stereotyped for any Ukrainian writer and is considered as both dominant and typological status and has always led him to spiritual dependence.